Sedimentation regime in distensible basins. Ayabaca limestones during the upper cretaceous (Ilave, Acora, Ayabaca, Mazo Cruz areas) located in southern Peru - Sánchez, José (2004)
Inside the Cretaceous stratigraphy of the Peruvian South Highlands, two clastic sequences can be distinguished, an inferior siliciclastic denominated Angostura Formation and a superior one, those ordered inside the Vilquechico and Muñani formations. These sequences are separated by a conspicuous carbonated level «Ayabacas Formation», which has the particularity of being presented in two ways: (a) a non-deformed, bed-growing, carbonated level, and (b) a level presenting an intense deformation, essentially made up of blocks of carbonates, where it is possible to distinguish both sandstone blocks and/or clasts, i.e. extraclasts. This particularity of this carbonated level had its origin in a distensional tectonics which favoured the olistrostomic character of these limestones.